Characterization of a sesquiterpene synthase and a short-chain dehydrogenase in zerumbone biosynthesis and the applications in engineered Saccharomyces cerevisiae - Xu, Mengdie; Xia, Yimeng; Fang, Gaowei; Li, Tangli; Ma, Jing; Li, Dengyu; Wei, Qiuhui; Tu, Lichan; Yin, Xiaopu; Hu, Tianyuan (Frontiers in Plant Science, 2025)
IntroductionZerumbone is a pharmacologically active sesquiterpenoid with limited availability. This study aims to elucidate its biosynthetic pathway in Curcuma wenyujin by identifying and characterizing the key enzymes responsible for its production.MethodsCandidate genes were selected via transcriptome analysis and phylogenetics. CwTPS8 and CwSDR1 were cloned and functionally characterized using in vitro enzyme assays and heterologous expression in engineered Saccharomyces cerevisiae. Molecular docking and site-directed mutagenesis were applied to investigate the catalytic mechanism of CwTPS8.ResultsCwTPS8 was identified as a multifunctional sesquiterpene synthase that catalyzes the formation of α-humulene (a key zerumbone precursor) and β-caryophyllene as main products, along with several minor sesquiterpenes. Mutagenesis studies identified critical residues (e.g., Thr437, Cys436) that significantly shift product specificity toward α-humulene. CwSDR1 was characterized as a short-chain dehydrogenase that efficiently oxidizes 8-hydroxy-α-humulene to zerumbone. A de novo biosynthetic pathway was reconstructed in yeast, resulting in zerumbone production at 0.50 μg/L.DiscussionThis study expands the genetic toolkit for zerumbone biosynthesis and provides insights into enzyme engineering and metabolic engineering strategies to enhance production. Limitations in precursor supply and catalytic efficiency highlight areas for future optimization.